Synesis as a framework to enable safety interventions in complex healthcare environments - Jamie Cargill; Aarti Bavare; Tiffany Wrenn; Anne Lam; Lauren Salinas; Itode Idowu; Asma Razavi; Venessa Lynn Pinto; Eric Williams (BMJ Open Quality)
Background Despite wide adoption in the healthcare of safety event report (SER) systems, there is a paucity of unified structures for prompt analysis and action while retaining reporter confidentiality. We used a synesis framework to change siloed reviews of safety reports to a comprehensive appraisal of quality, safety, productivity and reliability to facilitate interventions.Methods After a needs assessment survey, we launched serial plan-do-study-act cycles to (1) enhance teams’ ability to access SERs, (2) facilitate regular multidisciplinary review of SERs to identify actionable opportunities, (3) allocate action priority using failure mode and effects analysis, and (4) launch actions and summarise data. Team of Teams model allowed for empowered execution. Measures included process—completion of review, team engagement, proportion of ‘open’ (those without action plan) reports within 1 month of filing; outcome—number of actions launched and completed, dissemination of actions and postintervention survey results; and balancing—resources invested.Results 26 multidisciplinary leaders reviewed 3175 of the 3406 total reported SERs across four clinical units over 18 months. The proportion of reviewed to total SERs increased significantly from the first 6 months (75%) to the second 12 months (99%) (p<0.001), and the proportion of ‘open’ to reviewed SERs decreased significantly from 43% to 5.3% (p<0.001). Many local- and organisational-level actions were launched efficiently by the engaged and aligned team. Action impact was assessed by reviewing trends in SER themes and findings, and actions and impact were disseminated at unit, divisional and organisational levels. Postintervention survey showed improvement in leaders’ perceptions about SER reviews.Summary We successfully implemented a sustainable process to comprehensively review, prioritise and act on SERs in our large institution and facilitated safety interventions using a synesis framework.